2009
DOI: 10.3102/0002831209340043
|View full text |Cite
|
Sign up to set email alerts
|

National Income, Income Inequality, and the Importance of Schools: A Hierarchical Cross-National Comparison

Abstract: The international and comparative education literature is not in agreement over the role of schools in student learning. The authors reexamine this debate across 25 diverse countries participating in the fourth-grade application of the 2003 Trends in International Mathematics and Science Study. The authors find the following: (a) In most cases, family background is more important than schools in understanding variations in student performance; (b) schools are nonetheless a significant source of variation in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(85 citation statements)
references
References 33 publications
6
70
0
9
Order By: Relevance
“…Fuchs and Woessman (2007) found that approximately a quarter of the variation in performance between countries was due to the institutional characteristics of schools. The effect of these institutional characteristics varies considerably across countries (Chudgar & Luschei, 2009), supporting the argument of Suter (2000) that because countries vary in both educational institutions and educational performance, we have at least indirect evidence that educational policies can have a substantial effect on the overall performance of a nation's students.…”
Section: Efforts To Mitigate Educational Inequalitymentioning
confidence: 62%
See 2 more Smart Citations
“…Fuchs and Woessman (2007) found that approximately a quarter of the variation in performance between countries was due to the institutional characteristics of schools. The effect of these institutional characteristics varies considerably across countries (Chudgar & Luschei, 2009), supporting the argument of Suter (2000) that because countries vary in both educational institutions and educational performance, we have at least indirect evidence that educational policies can have a substantial effect on the overall performance of a nation's students.…”
Section: Efforts To Mitigate Educational Inequalitymentioning
confidence: 62%
“…The effect of family socioeconomic status (SES) was related to student achievement in the FIMS, indicating that the strong effect of family background noted in the contemporaneous Coleman Report (1966) was not restricted to the United States. More recent research has verified the continuing importance of family background to achievement in ILSAs (Baker et al, 2002;Woessman, 2004;Chudgar & Luschei, 2009;Montt, 2011). Methodological debates, particularly with respect to measuring SES, have resulted in varying estimates of SES-based inequality.…”
Section: Cross-country Differences In Within-country Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bazı araştırma sonuçlarına göre Türkiye gibi gelir dağılımının çok farklı olduğu ülkelerde öğrenci başarısında okul faktörü aile faktöründen daha önemli olmaktadır (Chudgar & Luschei, 2009). A.B.D.…”
Section: Tartişma Ve öNeri̇lerunclassified
“…Given the increasing importance of education in the knowledge society, one hypothesis is that parents with a higher level of education will put more emphasis on their children's development of knowledge and skills than parents with a lower level of education, and this difference will be more pronounced in countries with a high level of social and economic development than in countries with a lower level of development (e.g., Baker et al 2002;Chudgar and Luschei 2009;Chiu 2007;Heyneman and Loxley 1982). We thus expect the relation between parental education and student achievement to increase as a function of the country level of social and economic development.…”
Section: Previous Researchmentioning
confidence: 99%